CHARACTERIZATION OF ADOBE BLOCKS FROM BURGOS - Velosa, Ana; Varum, Humberto; Sáez, Maria (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2010)
Adobe was a building material of common use in construction practice in many areas of Spain. However, due to the introduction of new cement based building materials, it has been replaced and knowledge of the materials and techniques used for the construction of adobe buildings has been lost. In Spain earth based construction was widespread and common in northern regions such as Burgos, for example. This spatial distribution also encompasses a diversity of raw materials used in the execution of adobe blocks. In order to improve the knowledge on the composition of adobe blocks a set of specimens from the region of Burgos were sampled and studied. As a significant percentage of these buildings suffer from severe degradation, this knowledge can be used as a first step towards an adequate conservation practice that must be based on compatibility issues. For this purpose a testing campaign was performed, taking into account the mineralogical and chemical characterization of the adobe raw-materials and the mechanical and physical characterization of adobe blocks. There is a strong link between these raw materials and local availability, as adobe blocks were usually executed and consumed at a local scale.